HUBUNGAN PENGUASAAN KOSAKATA DAN KEBIASAAN MEMBACA DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA - Awwaabiin, Salmaa; Setiawan, Budhi; Wardani, Nugraheni Eko (Universitas Sebelas Maret, 2019)
This research is a correlation that aims to know (1) the correlation of vacabukary mastery with exposition text writing skills; (2) the correlation of reading habit with exposition text writing skills; (3) the correlation of vacabukary mastery and reading habit together with exposition text writing skills. The sample of this research are 128 students or 28% from 446 students, the total of population. The sampling technique that used is cluster random sampling. The data were collected using test method ang questionnaire. The rewuirements analysis that used is normality test. Meanwhile the data analysis that used are correlation (simple and double) and regression. The results of this study are: 1) positive and significant relationship of vocabulary mastery with the skills of writing exposition text shown with ry1 correlation coefficient of 0.45; 2) there is a positive and significant correlation of reading habits with expository text writing skills shown with ry2 correlation coefficient of 0.67; Â 3) there is a positive and significant relationship of mastery of vocabulary and reading habits together with the skills of writing expositional texts on the class students shown by the value of Ry.12 of 0.73 and the coefficient of determination of 0.53. Thus X1 Mastery of Vocabulary and X2 Reading Habits together contributes 53% to the skill of writing exposition texts